A coupled CFD-DEM numerical study of proppant transport in hydraulic fracture and natural fracture. (17th December 2022) - Ma, Li; Guo, Jianchun; Lu, Cong; Yang, Ruoyu; Mu, Kefan
Abstract: Based on computational fluid dynamics (CFD) and discrete element method (DEM), the factors affecting proppant transport law in hydraulic fracture and natural fracture are analyzed. The results indicated that the smaller the angle between hydraulic fracture and natural fracture, and the larger the width of natural fracture, the more proppants enter the natural fracture. As the viscosity of the fracturing fluid increases, the length of the "no proppant zone" in fracture is longer, and the proppant particles can be transported to a farther position. Proppant will quickly reach the fracture tip and be screened out under too high injection rate.